Rapeseed meal nutraceuticals - Syed Imran Hashmi; P.N. Satwadhar; R.R. Khotpal; H.W. Deshpande; K. A. Syed; B.P. Vibhute (Journal of Oilseed Brassica, 2026)
Many components of human diet previously overlooked are now considered to play an important role in theprevention and treatment of important diseases. Over the last decade disease preventing food and ingredients(called nutraceuticals) have written some success stories. Today the most important nutraceutical formulationscontain vitamins, with antioxidant properties, oligosaccharides, bioactive peptides, phenolic compounds,glucosinolates and other products. Studies showed that cruciferous seed meals that include rapeseed exertedprotective effects against tumour formation and growth. Rapeseed is reported to have a broad range oftherapeutic effects, including antioxidant, anti-inflammatory, antitumour and anticancer effect. The medicinalproperties of rapeseed are due to presence of variety of phytochemicals imparting the effect. In the laboratory,rapeseeds have been found to have very strong antioxidant activity, inhibiting cancer cell proliferation,decreasing lipid oxidation, and lowering cholesterol. While extensive research have been done, a literaturereview for health benefits of rapeseed meal and their phytochemicals has not been compiled to summarizethe investigations to provide a baseline for considering rapeseed meal in isolating nutraceuticals and developingfunctional food. This review attempts to report the medicinal properties of individual bioactive component,with the recent updates in vivo and in vitro research to explore the possibility of utilizing rapeseed meal indevelopment of functional food. The consideration of all the bioactive components of rapeseed meal isbeyond the purview of this review. Hence, only extensively studied major bioactive components viz. rapeseedphenolics, glucosinolates, dithiolthiones, phytates, phytosterols and bioactive peptides are considered.